An in silico study on inhibitability of Baloxavir marboxil, Baricitinib, Galidesivir, Nitazoxanide, and Oseltamivir against SARS‐CoV‐2. Issue 3 (17th May 2022) - Bui, Thanh Q.; Hai, Nguyen Thi Thanh; My, Tran Thi Ai; Phong, Nguyen Ho Vu; Nhan, Ngu Truong; Quy, Phan Tu; Nguyen, Nguyen Phuong Dai; Nhung, Nguyen Thi Ai
Abstract: Baloxavir marboxil (D1 ), Baricitinib (D2 ), Galidesivir (D3 ), Nitazoxanide (D4 ), and Oseltamivir (D5 ) are well‐known performing broad‐spectrum activity against a variety of viruses, thus holding high potentiality towards SARS‐CoV‐2. Quantum properties were examined using density functional theory (DFT). The inhibitability of the drugs towards Angiotensin‐converting enzyme 2 (ACE2) and SARS‐CoV‐2 main protease (6LU7) was evaluated by molecular docking simulation, while their bio‐compatibility was justified by physicochemical properties obtained from QSARIS‐based analysis in reference to Lipinski's rule of five. Quantum analysis suggests that the compounds are highly favourable for intermolecular interaction towards protein structures. Given ligand‐ACE2 systems, the inhibitory effectiveness follows the order D3‐ACE2  > D4‐ACE2  > D2‐ACE2  > D5‐ACE2  > D1‐ACE2 ; and the corresponding order for ligand‐6LU7 systems is D2‐6LU7  > D4‐6LU7  > D3‐6LU7  > D5‐6LU7  > D1‐6LU7 . Galidesivir is predicted as the most effective inhibitor towards both targeted protein structures (DSaverage ‐13.1 kcal.mol ‐1 ) and the most bio‐compatible molecule (Mass 264.9 amu; LogP ‐0.9; Polarisability 26.8 Å 3 ). The theoretical screening suggests all drugs, especially Galidesivir (D3 ), promising for treatment of SARS‐CoV‐2 infection and encourages in‐related clinical trials.